Blast performance of RC panels with waste steel fibers. (30th September 2015) - Foglar, Marek; Hajek, Radek; Kovar, Martin; Štoller, Jiří
Highlights: Fiber reinforced concrete shows better performance under blast and impact loading. Purpose-fabricated fibers are quite expensive. Use of cheap waste materials in structures subjected to blast loading is investigated. Low-ductility low-strength fibers had minimal effect on blast performance of FRC. Abstract: Due to its greater ductility, fiber reinforced concrete shows better performance under blast and impact loading than conventionally reinforced concrete. Common purpose-fabricated fibers are quite expensive and the use of more cost-effective waste materials in structures subjected to blast and impact loading should be investigated. This paper presents the results of field experiments focused on the effect of low ductility and low strength waste steel fibers, their combination with poly-propylene fibers on the blast performance of concrete. The combined effect of varied concrete compressive strength is also investigated. The tests were performed using real scale precast slabs (0.3 × 1.5 × 6 m) and 25 kg of TNT charges placed at a distance from the slab. Waste steel fibers added into the concrete mixture had a minimal effect on the blast performance of FRC. The results of the experiments were plotted on the spall and breach prediction curves; the RC specimens show good agreement with the spall and breach prediction curves. A numerical simulation of the experiment was performed. The results obtained from numerical modeling showed good agreement with the experimental results, and prove the preliminary estimates based on material performance.